Buddha in the crown : Avalokiteśvara in the Buddhist traditions of Sri Lanka - Holt, John, 1948- (Oxford University Press, 1991)
Sri Lanka has one of Asia's most pluralistic religious cultures. From a study of the changing role played by one Buddhist deity in Sinhala religious culture, the author of this study develops a thesis about the mechanism of religious change.